Tríplice invisibilidade de estudantes negras com altas habilidades / superdotação: narrativas no Instituto Federal do Amapá (IFAP), Macapá - ABAD, Thais Marluce Marques (2024)
Affirmative policies aim to address sectors of society that suffer from discrimination, injustice, racism, or exclusion. In the context of Special Education, Gifted and talented students (G&T) are often ignored or invisible to teachers, educational technicians, and society in general. This phenomenon is especially concerning when it comes to female students, particularly if they are black, a situation referred to as "triple invisibility." The problem is exacerbated by the lack of identification and referral of these students to the Nuclei for Assistance to People with Specific Educational Needs (NAPNE) in Federal Institutes. This study seeks to better understand these issues through an investigation at the Federal Institute of Amapá, Macapá campus, focusing on the narratives of G&T who self-identify as ethnically black. The research adopts a qualitative and exploratory approach. The sampling was non-probabilistic, with the participation of teachers and technicians from NAPNE, as well as two students who self-identified as black and were referred by teachers for exhibiting gifted behaviors. Semi-structured interview scripts were used for both the students and the pedagogical teachers/technicians. The results revealed several important issues: the lack of technical knowledge about giftedness and talent among teachers and educational technicians, challenges in identifying students with these abilities in the institute, the impact of the "Impostor Syndrome" on G&T black women, and the difficulties in implementing inclusion policies. As a result of this research, a short story was developed to disseminate information about the research results, using accessible language for all audiences. This educational resource aims to facilitate empowerment by providing information on rights, available resources, and strategies to overcome challenges, as well as raising awareness among the school community about the issues faced by G&T students.